Structure-antiviral activity relationship in the series of pyrimidine and purine N-[2-(2-phosphonomethoxy)ethyl] nucleotide analogues. 1. Derivatives substituted at the carbon atoms of the base - Holý, A; Günter, J; Dvoráková, H; Masojídková, M; Andrei, G; Snoeck, R; Balzarini, J; De Clercq, E (Journal of medicinal chemistry, 1999)
A series of dialkyl esters of purine and pyrimidine N-[2-(phosphonomethoxy)ethyl] derivatives substituted at position 2, 6, or 8 of the purine base or position 2, 4, or 5 of the pyrimidine base were prepared by alkylation of the appropriate heterocyclic base with 2-chloroethoxymethylphosphonate diester in the presence of sodium hydride, cesium carbonate, or 1,8-diazabicyclo[5,4, 0]undec-7-ene (DBU) in dimethylformamide. Additional derivatives were obtained by the transformations of the bases in the suitably modified intermediates bearing reactive functions at the base moiety. The diesters were converted to the corresponding monoesters by sodium azide treatment, while the free acids were obtained from the diester by successive treatment with bromotrimethylsilane and hydrolysis. None of the PME derivatives in the pyrimidine series, their 6-aza or 3-deaza analogues, exhibited any activity against DNA viruses or retroviruses tested, except for the 5-bromocytosine derivative. Substitution of the adenine ring in PMEA at position 2 by Cl, F, or OH group decreased the activity against all DNA viruses tested. PMEDAP was highly active against HSV-1, HSV-2, and VZV in the concentration range (EC50) of 0.07-2 microg/mL. Also the 2-amino-6-chloropurine derivative was strongly active (EC50 = 0.1-0. 4 microg/mL) against herpes simplex viruses and (EC50 = 0.006-0.3 microg/mL) against CMV and VZV. PMEG was the most active compound of the whole series against DNA viruses (EC50 approximately 0.01-0.02 microg/mL), though it exhibited significant toxicity against the host cells. The base-modified compounds did not show any appreciable activity against DNA viruses except for 7-deazaPMEA (IC50 approximately 7.5 microg/mL) against HIV-1 and MSV. The neutral (diisopropyl, diisooctyl) diesters of PMEA were active against CMV and VZV, while the corresponding monoesters were inactive. The diisopropyl ester of the 2-chloroadenine analogue of PMEA showed substantially (10-100x) higher activity against CMV and VZV than the parent phosphonate. Also, the diisopropyl and diisooctyl ester of PMEDAP inhibited CMV and VZV, but esterification of the phosphonate residue did not improve the activity against either MSV or HIV.
Keywords: Cell Line; DNA viry; Anti-HIV Agents; HIV-1; antivirové látky; Purine Nucleotides; Organophosphonates; pyrimidinové nukleotidy; zvířata; vztahy mezi strukturou a aktivitou; Humans; Pyrimidine Nucleotides; HIV-2; purinové nukleotidy; Moloney murine sarcoma virus; látky proti HIV; DNA Viruses; buněčné linie; Antiviral Agents; Moloneyho virus myšího sarkomu; organofosfonáty; Structure-Activity Relationship; lidé; Animals